2018
DOI: 10.1111/eea.12651
|View full text |Cite
|
Sign up to set email alerts
|

Suitability of brachiaria grass as a trap crop for management ofChilo partellus

Abstract: The cereal stemborer Chilo partellus (Swinhoe) (Lepidoptera: Crambidae) is a major insect pest of sorghum (Sorghum bicolor L. Moench) and maize (Zea mays L.) in Africa. Trap cropping systems have been shown to be a valuable tool in management of this pest. To optimize trap cropping strategies, an understanding of host‐plant preference for moth oviposition and host suitability for larval survival on potential trap plants is a prerequisite. Therefore, we assessed seven brachiaria accessions (Poaceae) for prefere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 69 publications
1
16
1
Order By: Relevance
“…Mulato II and B. brizantha ( Table S2 ). The values found for these species are lower than those reported by Cheruiyot et al [ 61 ]. Except for Mombasa, the trichome density decreased from the leaf base to the leaf apex, as reported by Rendón-Carmona et al [ 38 ].…”
Section: Discussioncontrasting
confidence: 80%
“…Mulato II and B. brizantha ( Table S2 ). The values found for these species are lower than those reported by Cheruiyot et al [ 61 ]. Except for Mombasa, the trichome density decreased from the leaf base to the leaf apex, as reported by Rendón-Carmona et al [ 38 ].…”
Section: Discussioncontrasting
confidence: 80%
“…Samples were obtained from the intermediate position between leaf margin and midrib of the leaf lamina and halfway between proximal end and base of the leaf, from the leaves 6 and 7 of three weeks old plants. Trichomes were counted with a stereo microscope (Stemi 508 Carl Zeiss; Jena, Germany) with a magnification of 25×, moistening slightly the leaf cut [ 49 ].…”
Section: Methodsmentioning
confidence: 99%
“…Plant to plant communication is known to be a mechanism of pest control through herbivore-induced plant volatiles (HIPVs) (Khan et al 2001;Cook et al 2007;Heil 2008;Tamiru et al 2012;Magara et al 2015;Mutyambai et al 2016). Studies have shown that B. brizantha is preferred to maize for oviposition by gravid C. partellus (Midega et al 2011;Cheruiyot et al 2018). This is as a result of B. Brizantha leaves emitting more green-leaf volatiles signals ((Z)-3-hexenyl acetate) which are the responsible cues for attracting gravid females of C. partellus to the grass to deposit eggs compared to maize (Bruce et al 2010;Magara et al 2015;Tolosa et al 2019).…”
Section: Introductionmentioning
confidence: 99%